2023
DOI: 10.3389/fcimb.2023.1126516
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps promote bronchopulmonary dysplasia-like injury in neonatal mice via the WNT/β-catenin pathway

Abstract: BackgroundBronchopulmonary dysplasia (BPD) is one of the most common and severe chronic diseases in preterm infants. Premature infants are susceptible to BPD due to immature lungs and adverse perinatal episodes of infection, hyperoxia, and mechanical ventilation.MethodsNeutrophils are the first line of host defence, and the release of neutrophil extracellular traps (NETs) is an important strategy to immobilize and kill invading microorganisms. This study examined whether NETs were associated with BPD in preter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“… 26 Recently, it was reported that neutrophil extracellular traps (NETs) could promote BPD progression via the Wnt/β-catenin pathway. 49 As NETs are released by activated neutrophils, it is possible that CD62L − neutrophil subset promotes BPD progression via NETs. Further experiments are required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Recently, it was reported that neutrophil extracellular traps (NETs) could promote BPD progression via the Wnt/β-catenin pathway. 49 As NETs are released by activated neutrophils, it is possible that CD62L − neutrophil subset promotes BPD progression via NETs. Further experiments are required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%